(untitled) (Journal of Atomic and Molecular Sciences, 2014)
We present a theoretical analysis of the influence of shock wave propagating in bubble cluster and bubble combining in expansion phase on maximum temperature inside central bubbles. By using adiabatic model and assumptions for simplifying the problem we find that these parameters have significant effects on temperature rising in compression phase. In particular, the shock wave, in comparison to bubble combining, has a greater impact on the maximum temperature.